Age affects drug survival rates of interleukin (IL)-17 and IL-23 inhibitors in patients with plaque psoriasis: Results from a retrospective, multicentric, multi-country, cohort study - Chiricozzi, Andrea; Coscarella, Giulia; Puig, Luis; Vender, Ron; Yeung, Jensen; Carrascosa, José-Manuel; Piaserico, Stefano; Gisondi, Paolo; Lynde, Charles; Ferreira, Paulo; Bastos, Pedro Mendes; Dauden, Esteban; et al. (Journal of the European Academy of Dermatology and Venereology, 2024)
BACKGROUND: Scarce data related to the drug survival of biologic agents in psoriasis patients aged ≥65 years is available. OBJECTIVES: To evaluate the drug survival of interleukin (IL)-23 or the IL-17 inhibitors approved for the treatment of moderate-to-severe psoriasis in elderly patients (aged ≥65 years), compared with younger adult patients (aged <65 years), and to identify clinical predictors that can influence the drug survival. METHODS: This retrospective multicentric cohort study included adult patients with moderate-to-severe psoriasis, dissecting two-patient subcohorts based on age: elderly versus younger adults. Kaplan-Meier estimator and proportional hazard Cox regression models were used for drug survival analysis. RESULTS: We included 4178 patients and 4866 treatment courses; 934 were elderly (1072 treatment courses), and 3244 were younger patients (3794 treatment courses). Drug survival, considering all causes of interruption, was higher in patients aged <65 years than in elderly patients overall (log-rank p < 0.006). This difference was significant for treatment courses involving IL-23 inhibitors (p < 0.001) but not for those with IL-17 inhibitors (p = 0.2). According to both uni- and multi-variable models, elder age was associated with an increased risk of treatment discontinuation (univariable analysis: HR: 1.229, 95% CI 1.062-1.422; p < 0.006; multivariable analysis: HR: 1.199, 95% CI 1.010-1.422; p = 0.0377). Anti-IL-23 agents were associated with a reduced likelihood of treatment discontinuation after adjusting for other variables (HR: 0.520, 95% CI 0.368-0.735; p < 0.001). Being previously treated with IL-17 inhibitors increased the probability of discontinuation. CONCLUSIONS: Elderly patients with psoriasis have an increased risk of biologic treatment discontinuation compared with younger adult patients, particularly, if being treated with IL-23 inhibitors. However, in stratified analyses conducted in elderly patients, IL-23 inhibitors showed higher drug survival rates than IL-17 inhibitors.
Keywords: interleukin-23; Interleukin-17; Aged; Dermatologic Agents; Retrospective Studies; Age Factors; lidé středního věku; senioři; humanizované monoklonální protilátky; psoriáza; interleukin-17; lidé; Adult; Middle Aged; Antibodies, Monoclonal, Humanized; dospělí; Psoriasis; Female; věkové faktory; Male; ženské pohlaví; Humans; mužské pohlaví; dermatologické látky; Interleukin-23; retrospektivní studie